International Organizations - Schiavone, Giuseppe. author. aut Link
V, 321 p.
Keywords: A new edition of a dictionary of international organisations, last published in 1992, which provides an unbiased review of over 200 organisations currently in existence, with membership charts for the UN, specialised agencies and regional institutions, and a table of foundation dates.